Evaluating the response of Schizothorax prenanti to ammonia nitrogen stress using computer vision and transcriptomics - Yinhua Zhou; He Gao; Hejiao Li; Tianyi Shen; Yifan Yao; Zhilei Wang; Yuting Duan; Junting Li; Suxing Fu; Shidong Liu; Rongrong Liao; Haiping Liu; et al. (Aquaculture Reports)
The tolerance and response to ammonia nitrogen have not been studied in Schizothorax prenanti (S. prenanti), an important economic fish in southwest China. This study, for the first time, combines behavioral, histological, biochemical, and transcriptomic analyses to explore its response to ammonia nitrogen stress. Acute toxicity tests showed that the 96 h LC50 TAN (total ammonia nitrogen) in S. prenanti was approximately 16 mg/L (temperature = 21°C, pH = 7.5). Behavioral quantification using YOLO v8 (You Only Look Once version 8) indicated no significant impact under low-concentration stress (L, 30 % LC50); medium-concentration stress (M, 45 % LC50) significantly enhanced the swimming speed, exercise volumes, and localized activity, and high-concentration stress (H, 60 % LC50) caused abnormal behavior and restricted activity. Gill histology and TUNEL assay revealed epithelial swelling and curling of secondary filaments under low-concentration stress. Medium-concentration stress caused localized structural damage and cell apoptosis and high-concentration stress induced severe necrosis and apoptosis in the secondary filaments. Biochemical tests showed significant increases in plasma cortisol, glucose, plasma ammonia, and tumor necrosis factor-α under high-concentration stress. Gill superoxide dismutase, catalase, and total antioxidant capacity activities were significantly decreased and malondialdehyde levels were increased. Transcriptomic analysis indicated that most differentially expressed genes (DEGs) in the M and H groups were enriched in pathways related to immune response, antioxidation, carbohydrate metabolism, and amino acid metabolism. Notably, DEGs related to the TCA cycle and oxidative phosphorylation were enriched in the M group, likely to provide energy for immune response and ammonia detoxification. Suppression of antigen processing and presentation may explain why S. prenanti struggles to cope under high ammonia nitrogen stress. S. prenanti shows a certain tolerance to ammonia nitrogen, however, concentrations exceeding 9.6 mg/L result in behavioral abnormalities, gill tissue damage, oxidative stress, apoptosis, and immune suppression. The findings provide a theoretical foundation for research on the tolerance and response of S. prenanti to ammonia nitrogen and offer a new perspective for monitoring and managing ammonia nitrogen stress in intensive aquaculture systems.